Socialization of Positive Internet Use for Children - Harry Idwan; Zahrul Maizi; Rahmi Hajriyanti (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
The purpose of this activity is to provide an understanding for parents of students and children to monitor internet use and find out its positive and negative impacts. Service activities only involve 2 stages of activity, the first is socialization and the second is discussion. This community service activity is intended so that parents and the community can understand and monitor the use of the internet for children. Activities that have been carried out are in the form of socializing positive internet use for children with 70 participants from Banda Aceh City. The usefulness of this community service activity is evaluated through a questionnaire with a benefit test. The results of the questionnaire show a percentage of 67% which states that the socialization of internet use in children is very useful to be applied in real life today.